The combination of dietary active dry yeast and Bacillus subtilis improves productive performance, egg quality, and immunity of aged breeder hens - Yuchen Liu; Xintong Wang; Xiaoyu Zhao; Ying Ma; Lujiang Qu; Zhong Wang; Zhonghua Ning (Animal Nutrition)
This study aimed to investigate the effects of dietary supplementation with active dry yeast (ADY) alone or in combination with Bacillus subtilis (BS) on physiological parameters (laying performance, egg quality, blood indexes), reproductive traits, ileum microbiome, metabolome, and uterine gene expression in aged breeder hens. A total of 336 Hy-line brown layer hens aged 55 weeks were randomly assigned to three groups using a completely randomized design: control group (Con, basal diet), ADY group (1 g ADY/kg diet), and ADY-BS combination group ([1 g ADY + 0.1 g BS]/kg diet). Compared with the Con group, ADY-BS group significantly improved egg production (P = 0.024) and reduced feed conversion ratio (P = 0.034), while also significantly increasing feed intake compared to the ADY group (P = 0.020). Additionally, both ADY and ADY-BS significantly enhanced eggshell-breaking strength compared to untreated hens (P < 0.001), with ADY-BS further notably increasing lysozyme levels (P = 0.031), antibody titers against avian influenza H5 and H9 subtypes (P = 0.008 and P = 0.001, respectively), and calcium content in serum (P = 0.021). Analysis of the ileal microbiota revealed significant modifications, as evidenced by reduced richness (Chao1 index: P = 0.016 and P = 0.008 for the ADY and ADY-BS groups, respectively) and improved evenness (Simpson index: P = 0.032 for both groups). Relative to the untreated group hens, ADY enriched Streptococcus (P = 0.007), Enterococcus (P = 0.009), and Gallibacterium (P = 0.027), whereas ADY-BS remarkably enriched Lactobacillus (P = 0.028). Furthermore, Lactobacillus enriched in ADY-BS group hens was negatively correlated with ileum differential metabolites such as phenylalanyl-threonine and phenylalanyl-tryptophan. Correlation analysis based on RNA-seq data indicated that these differential metabolites were negatively associated with the expression of genes related to calcium ion transport and immune pathways in the uterus. In summary, the results suggest that ADY-BS combination significantly improved production performance, eggshell quality, gut microenvironment, and immune function compared to ADY alone in late-laying hens.